2020
DOI: 10.21640/ns.v12i25.2466
|View full text |Cite
|
Sign up to set email alerts
|

Relación entre autoeficacia, apoyo social, adherencia al tratamiento y HbA1C por nivel de percepción de amenaza en pacientes con DM2

Abstract: Introduction: The main problem presented by patients with DM2 is the lack of adherence to medical treatments (WHO, 2004) since it is complex and requires changes in lifestyle and health habits. Objective: analyze the relationship between self-efficacy, social support, and threat perception to treatment adherence.Method: The design was transectional correlational with a non-probabilistic convenience sampling of 166 participants with DM2 who attended for medical attention at the Ministry of Health and ISSSTE of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
1
0
0
1
Order By: Relevance
“…Moreover, the present study identifies a positive correlation between treatment adherence and self-efficacy, indicating that those who more faithfully follow their treatments tend to have greater confidence in their ability to do so. Like that reported by a study [25] of chronic patients in Michoacán, Mexico, which analyzed the relationship between self-efficacy, perceived social support, and adherence to treatment The results showed that self-efficacy was directly related to lower levels of noncompliance and greater perceived social support. In addition, mediational analyses indicated that self-efficacy had a significant direct and indirect effect (through perceived social support and satisfaction with support) on patients' adherence, specifically in relation to diet and physical exercise.…”
Section: Discussionsupporting
confidence: 50%
“…Moreover, the present study identifies a positive correlation between treatment adherence and self-efficacy, indicating that those who more faithfully follow their treatments tend to have greater confidence in their ability to do so. Like that reported by a study [25] of chronic patients in Michoacán, Mexico, which analyzed the relationship between self-efficacy, perceived social support, and adherence to treatment The results showed that self-efficacy was directly related to lower levels of noncompliance and greater perceived social support. In addition, mediational analyses indicated that self-efficacy had a significant direct and indirect effect (through perceived social support and satisfaction with support) on patients' adherence, specifically in relation to diet and physical exercise.…”
Section: Discussionsupporting
confidence: 50%
“…No obstante, a pesar de estas limitaciones, algunas organizaciones como la IDF o la American Diabetes Association (ADA, 2021) han considerado tres criterios diagnósticos para la DM2: muestra de glucemia plasmática al azar (> 200 mg/dl) o dos muestras seguidas con cifras > 126 mg/dl en ayuno, sobrecarga oral de glucosa luego de 2 h (> 200 mg/dl) y hemoglobina glucosilada (HbA1c) < 7 7,8 . Estos criterios asociados al control glucémico permiten utilizar diversos modelos orientados a generar cambios sobre la adhesión de estilos de vida saludables, además de tratamientos que incluyan medicamentos hipoglucemiantes no insulínicos e insulinoterapia cuando los métodos anteriores no logran un control glucémico deseado 8,9 La insulinoterapia se ha utilizado ampliamente debido al aumento en la prevalencia de DM2, por lo que un adecuado manejo es un factor fundamental dentro de las pautas de tratamiento. Su uso cobra relevancia por la existencia de una relación entre un adecuado control glucémico y un bajo riesgo de complicaciones de salud como lo es la lipohipertrofia en pacientes con DM2.…”
Section: Introductionunclassified